Some Methods for Managing the Degradation of Biomedical Implantable Materials Based on Collagen and Hyaluronic Acid - Rudik, I.S.; Vasiliev, A.V.; Mironov, A.V.; Kuznetsova, V.S.; Losev, F.F. (Biomedical Chemistry: Research and Methods, 2025)
The review considers modern approaches to modifying the in vitro degradation kinetics of implantable matrices based on collagen and hyaluronic acid. It includes data presented in 24 of approximately one hundred articles on similar topics found. Special attention is paid to the effect of polymer additives in collagen- and hyaluronic acid-based materials on their degradation rates in hydrolytic and enzymatic environments. The mechanisms of interaction of components and the impact of their structure on degradation processes are described. Approaches to the development of implantable medical devices based on biopolymers with controlled degradation and biocompatibility properties are proposed.